PENENTUAN PATOTIPE DAN KERAGAMAN GENETIK Xanthomonas oryzae pv. oryzae PADA TANAMAN PADI DI WILAYAH KARESIDENAN BANYUMAS - Heru Adi Djatmiko; Budi Prakoso; Nur Prihatiningsih (Universitas Lampung, 2011)
One of the major diseases of rice paddy fields in Indonesia and the Asian countries is bacterial leaf blight or kresek caused by X. oryzae pv. oryzae (Xoo). Losses caused by the disease in Indonesia reached 70–80%, in India reached 74–81%, and Japan reached 20–50%, thus causing great losses in the economy. The objectives of that research were: 1) Characterize Xoo from Karesidenan Banyumas; 2) To study of the amount of damage and AUDPC (the area under disease progress curve) of bacterial leaf blight disease at Karesidenan Banyumas; 3) To obtain of Xoo pathotype by using the test varieties; 4) To obtaining genetic diversity of Xoo that found in Banjarnegara, Purbalingga, Banyumas, Cilacap dan Kebumen region. Research was carried out in several stages: isolation and characterization of Xoo from Barlingmascakeb region, testing of Xoo with five varieties testing, assesment of disease intensity of bacterial leaf blight and AUDPC in the field, and testing the genetic diversity of Xoo. The results showed that pathogen of bacterial blight on rice is Xoo characterized yellow colour of colonies on SPA medium, negative gram reaction, catalase positive, oxidase negative, negative growth at 0.1% TZC, negative starch hydrolisis , and resistance to 0.001% Cu(NO3)2 positive. Xoo pathotype isolats found in Banjarnegara was pathotype X, Cilacap were pathotype I and II and Purbalingga was pathotype II. Eighteen of Xoo from Karesidenan Banyumas (Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen) of RAPD differ one from the others.